Investigation of the underuse of adrenaline (epinephrine) and prognosis among patients with anaphylaxis at emergency department admission - Yen-Yue Lin; Yen-Yue Lin; Yen-Yue Lin; Hsin-An Chang; Yung-Hsi Kao; Chih-Pin Chuu; Chih-Pin Chuu; Wen-Fang Chiang; Wen-Fang Chiang; Ya-Chieh Chang; Ya-Chieh Chang; Yuan-Kuei Li; et al. (Frontiers in Medicine, 2023)
BackgroundAnaphylaxis is a potentially fatal condition; in severe cases of anaphylaxis, the cardiovascular system is often heavily involved. Adrenaline (epinephrine) is a cornerstone of the initial treatment of anaphylaxis. The use of epinephrine remains below expectations in clinical practice. Whether the underuse of epinephrine affects the prognosis of patients with anaphylaxis is still unclear.Materials and methodsThis retrospective study included patients with anaphylaxis between 2011 and 2020 who were admitted to an emergency department (ED) in Taiwan. All patients were divided into two groups based on the use of epinephrine (or not), and we compared the demographic characteristics, allergens, clinical manifestations, management, and patient outcomes.ResultsWe reviewed the records of 314 subjects (216 males, 98 females; mean age: 52.78 ± 16.02 years) who visited our ED due to anaphylaxis; 107 (34.1%) and 207 (65.9%) patients were categorized into the epinephrine use group and the non-epinephrine use group, respectively. Arrival via ambulance (p = 0.019), hypotension (p = 0.002), airway compromise (p < 0.001) and altered consciousness (p < 0.001) were the deciding factors for epinephrine use among anaphylactic patients in the ED. The epinephrine use group had higher rates of other inotropic agent usage and fluid challenge. More than 90% of patients received bed rest, steroids, antihistamines, and monitoring. The epinephrine use group had a longer ED length of stay (387.64 ± 374.71 vs. 313.06 ± 238.99 min, p = 0.03) and a greater need of hospitalization. Among all severe symptoms, hypotension was the most tolerated decision factor for not using epinephrine. In this retrospective analysis, some patients with serious anaphylaxis did not experience adverse outcomes or death even without the use of epinephrine at ED admission. Emergent care focuses first on the airway, breathing, and circulation (ABC) and may compensate for the underusage of epinephrine. This could be the reason why epinephrine was underused among patients with anaphylaxis in the ED.ConclusionIn summary, early ABC management continues to play an important role in treating patients with severe anaphylaxis, even when epinephrine is not immediately available in clinical scenarios.